"Biopolitics on Screen”: Aernout Mik’s Moving-Image Installations - Calchi-Novati, Gabriella (Cinema: Journal of Philosophy and the Moving Image, 2011)
In this paper I propose that the moving-image installations Vacuum Room (2005), Scapegoats (2006), Training Ground (2006), and the most recent Shifting Sitting (2011), produced by Dutch artist Aernout Mik, are performative instances of current biopolitical concerns. These video installations represent what is supposed, and, more crucially, is always expected to be unrepresentable, namely what Zygmunt Bauman calls “constant uncertainty,” which can be considered one of the by-products of biopolitics. It is because of this uncertainty that we feel hopeless in relation to the political status quo and we are made believe, as Bauman contends, “that everything can happen but nothing can be done”. I argue that these works, when considered “as-philosophy,” or “philosophy-in-motion,” function as a series of conceptual paradigms that illustrate the main thesis of this paper, namely, that these very same installations, seen through Giorgio Agamben’s philosophical lens, are in fact biopolitics on screen.